Short‐Term Effects of Attaching Animal‐Borne Devices on the Behavior of Juvenile Green Turtles - Nathan J. Robinson; Ruth Doñate‐Ordóñez; Damianos Chatzievangelou; Annabelle M. L. Brooks; Jack Cuffley; Candace Y. A. Fields; Sebastian Hoefer; Theodora Pinou; Alexander Smith; Sophie Mills (Ecology and Evolution)
ABSTRACT The use of animal‐borne devices (= biologgers) has revolutionized the study of marine megafauna, yet there remains a paucity of data concerning the behavioral and physiological impacts of biologger attachment and retention. Here, we used animal‐borne cameras to characterize the behavior and dive duration of juvenile green turtles (Chelonia mydas) in The Bahamas for up to 210 min after biologger deployment (n = 58). For a “control,” we used unoccupied aerial vehicles (UAVs) to collect comparable data from nonhandled green turtles (n = 25) in the same habitats. Animal‐borne footage revealed that immediately after release turtles spent 70%–80% of their time swimming with a mean dive duration of 45.3 ± 34.3 s (SD). Over time, the percentage of time spent swimming decreased alongside an increase in dive duration until reaching a plateau around 90 min. However, the “control” UAV data for time spent swimming and dive durations were more comparable to the behaviors observed immediately after biologger deployment than during the plateau. We observed no significant differences in dive durations based on body size, and differences in behaviors based on body size were also minimal. We conclude that the effects of handling stress and biologger attachment on the behavior and dive duration of juvenile green turtles are evident up to 90 min postdeployment. After that, it is possible that either: (1) the effects of biologger deployment and retention are negligible, but UAVs may produce biased data that overestimates the proportion of time turtles typically spend swimming or (2) longer durations (> 210 min) are necessary for turtle behaviors to return to nonhandled levels and UAVs accurately represent the proportion of time turtles typically spend swimming. Answering this question, alongside further research into the physiological and behavioral implications of handling stress and biologger attachment, is essential to improve ethical biologging guidelines for sea turtles.